Sensing mispaired thymines in DNA heteroduplexes using an electroactive osmium marker: towards electrochemical SNP probing - Kostečka, Pavel; Havran, Luděk; Bittová, Miroslava; Pivoňková, Hana; Fojta, Miroslav (Analytical and bioanalytical chemistry, 2011)
A complex OsO(4), 2,2'-bipyridine (Os,bipy), has been used for electroactive labeling of biopolymers as well as for probing of nucleic acids and protein structure and interactions. In DNA, Os,bipy forms electrochemically active adducts with pyrimidine nucleobases, exhibiting highly selective modification of thymine residues in single-stranded DNA. Here, we show that modification of rare thymine residues (one thymine among several tens of unreactive purine bases) can easily be detected by means of a simple ex situ voltammetric analysis using carbon electrodes. Based on this remarkable sensitivity of detection, Os,bipy has been used as an electroactive probe for unpaired and/or mismatched thymine residues within DNA heteroduplexes. Site-specific chemical modification of the DNA with the Os,bipy has allowed a clear distinction between perfectly base-paired DNA homoduplexes and mismatched heteroduplexes, as well as discrimination among heteroduplexes containing one or two mispaired thymines, a single thymine insertion, or combination of a mispair and an insertion.
Keywords: DNA; DNA sondy; Nucleic Acid Heteroduplexes; jednonukleotidový polymorfismus; Osmium; Polymorphism, Single Nucleotide; Thymine; elektrochemie; heteroduplexy nukleové kyseliny; Base Sequence; Electrochemistry; DNA Probes; thymin; sekvence nukleotidů; osmium